Energy‐efficient network design via modelling: optimal designing point for energy, reliability, coverage and end‐to‐end delay. Issue 1 (1st March 2013) - Ansari, Mohammad Saeed; Mahani, Ali; Kavian, Yousef S.
Abstract : Considering that practical wireless sensor networks are mostly built upon energy‐constrained sensor nodes, network lifetime becomes a key deployment factor for sustainability of such networks initiating an attempt for prolonging the lifetime. Adopting a new multi‐mode switching protocol for sensor nodes between active and sleep states, in this study, the authors propose a new mathematical method using an embedded simulation‐based computing of an energy‐efficient strategy performance metric to maintain resiliency of the network against side effects appearing in duty‐cycling protocols. Here, the authors use a Monte Carlo simulation to estimate network reliability. Then the proposed mathematical model enables us to build a decision for optimised performance upon trade‐offs between consumed energy, reliability, coverage intensity and end‐to‐end delays by locating a network's operational points. The authors show the trade‐off operational significance of the model against the percentage of sleeping probability via some design factors including figure of merit.